Exploring feminist notions of peacebuilding: experiences of women activists in Northern Uganda - Clarke, Yaliwe (Department of Social Development, 2022)
This qualitative study was undertaken in Northern Uganda, specifically in the districts of Gulu, Lira, and Kitgum. The researcher spent a total of six months collecting field data (over a period of 2 years) from key members of community-based peacebuilding groups as well as from the groups' beneficiaries. This study conceptualised gender from a decolonial, intersectional framing of femininities which considered lineage, age, class, and geographic location of women who founded peace groups during and just after some of the most volatile periods of the war in Northern Uganda. The researcher theorised how women's small- scale community interventions manifested as part of broader peacebuilding efforts undertaken by larger institutions such as government and international development organisations that were present in Northern Uganda at the time of the study. Based on in-depth interviews with seventeen founders and staff of six community-based peace groups as well as seven focus group discussions with 76 beneficiaries, the study explored shifting gendered subjectivities performed across multiple roles and identities. The data collected was further enhanced by follow-on interviews with seven people who worked with larger aid organisations that interacted with the six community-based peace groups. The researcher reviewed organisational documents such as project reports and minutes of staff meetings to corroborate research participants' narration of their community work. Using thematic analysis, the study deconstructs participants' ‘gendered' meanings of peacebuilding. The findings from this study suggest that an African feminist perspective to peacebuilding requires the following: a nuanced intersectional analysis of women's socio-economic and political power within militarised contexts; foregrounding local efforts to build peace by focusing on gendered experiences of survival; a recognition of militarism as a social and economic system that is often intertwined with colonial histories of violence as well as patriarchal values and customs that present masculine power as normative; and finally, unpacking shifts in gendered power, especially with regard to markers of socio-economic and political power.